The results of one year monitoring the water quality of the Barje reservoir - chemical aspects - Cibulić, Violeta; Petrović, Veselin (Macedonian Journal of Ecology and Environment, 1997)
After the Barje reservoir had been completely formed and its maximum volume had been achieved (April 199.5), abiotic and biotic components of the aquatic ecosystem were investigated during a year term (1996). From the systematic monitoring of the physic and chemical characteristics of the water in one-month intervals, an effort was made to define the water quality from the chemical aspects. Since the reservoir was built primarily for the water supply (the city of Leskovac and the settlements of the Leskovac and Lebane communities), these investigations, carried out monthly (the physic and chemical aspects) and seasonally (the biological aspect), were aimed to consider the water quality and to plan the technical and biological measures in the area of the Barje reservoir and the river basin for the purpose of their protection.